The basal membrane destruction in benign prostatic hyperplasia, prostatic intraepithelial neoplasma, and prostatic adenocarcinoma. A study on basal membrane type IV collagens - Irianiwati, Irianiwati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Basal membrane (BM), a selective permeable membrane is mainly composed of type IV collagen. A tumor invasion, therefore, may only occur if this membrane is destroyed by an active process of tumor producing proteolytic enzymes. It has been found that prostatic intraepithelial neoplasia (PIN) is a prostatic premalignant lesion. Although both benign prostate hyperplasia (BPH) and prostatic adenocarcinoma required an androgenic hormone for their growth, the correlation between the degree of destruction of basal membranes and BPH, PIN, and prostatic adenocarcinoma should be clarified. This can be studied by observing the continuity of periacinair BM. In order to understand the correlation among prostatic lesions, the BM continuity of 40 paraffin block specimens (15 BPH, 11 PIN, and 14 Prostatic adenocarcinomas) were studied. The BM of these specimens were stained immunohistochemically with MoAB anti human Type IV collagens. The periacinair BM continuity was scored 0-5. The Spearmans correlation test was used to analyze their possible relationship.The result shows that there is a significant correlation between the degree of destruction of basal membranes and BPH, PIN, and Prostatic adenocarcinomas (r = 0.898; p<0.05). In conclusion, based on periacinair BM des-truction, there is a positive correlation between the degree of destruction of basal membranes and BPH, PIN, and prostatic adenocarcinomas.Key words : collagen type IV - prostatic adenocarsinoma - prostatic intrapithelial neoplasia - benign prostate hyperplasia - basal membrane